Expert System to Determine Learning Style Using Forward Chaining Method - Cahya, Dela Yunita; Oktaviana, Shinta (MULTINETICS, 2018)
Abstract - The expert system of learning modalities determination is a system that adopts the knowledge of an educational psychologist in determining the learning modalities that are appropriate to the child's personality. This expert system is made by forward chaining method and uses the expert Certainty Factor (CF) value. The purpose of this expert system is to prove that forward chaining method can be implemented in making this expert system. Furthermore, expert system can provide benefits to assist an educational psychology in Bahana Psikologi Pelangi (BPP) in performing the determination test of visual modalities, auditory or kinesthetic. Data obtained by conducting interviews and based on questionnaires in BPP in determining a person's learning modalities. Implementation of forward chaining method with the implementation of CF value is important in determining the conclusion of modalities and suggestions that will be recommended. The end result of this expert system is the highest CF value of each modality. Tests on the system performed by comparing the conclusions of modalities on expert systems with the conclusion of modalities on the calculation of manual questionnaires in BPP. Based on the 53 questionnaires used, there are 42 data showing the same modalities conclusion with manual process, while 11 of them show different result because of the priority of CF value in expert system.